2016
DOI: 10.5964/ejop.v12i4.1159
|View full text |Cite
|
Sign up to set email alerts
|

With a little help from my family: A mixed-method study on the outcomes of family support and workload

Abstract: Our aim was to investigate some predictors and outcomes of family-to-work enrichment (FWE) via a mixed-method approach. We sampled 447 married employees of an Italian factory. Survey results from Study 1 showed that emotional support from family positively predicted FWE, while this latter mediated the associations between the former on one side, and work engagement and life satisfaction on the other. Moreover, extra-household support directly associated positively with life satisfaction. Evidence from 20 anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
2
16
0
2
Order By: Relevance
“…These are working conditions that concern different family aspects such as family workload (i.e., a family demand) and family social support (i.e., a family resource). As for family resources, it has been shown that they have a predictive role with respect to enrichment [ 38 ], as well as family support that seems to have fundamental variables that can either favor or hinder the FWE development [ 35 ]. Likewise, Bhargava and Baral [ 19 ] identified family support as an antecedent of WFE, while in a meta-analytical review [ 34 ], family role, overload family stressors, and family demands, together with supportive antecedents such as spousal support and familiar climate, were found to have significant effects on the conflict.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…These are working conditions that concern different family aspects such as family workload (i.e., a family demand) and family social support (i.e., a family resource). As for family resources, it has been shown that they have a predictive role with respect to enrichment [ 38 ], as well as family support that seems to have fundamental variables that can either favor or hinder the FWE development [ 35 ]. Likewise, Bhargava and Baral [ 19 ] identified family support as an antecedent of WFE, while in a meta-analytical review [ 34 ], family role, overload family stressors, and family demands, together with supportive antecedents such as spousal support and familiar climate, were found to have significant effects on the conflict.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Family life may affect work outcomes anywhere (e.g., Lo Presti, D'Aloisio, & Pluviano, ). Wayne, Grzywacz, Carlson, and Kacmar () delineated three main functions of the family with regard to its working members: (a) supporting the achievement of personal and job‐related goals; (b) addressing job demands by buffering emotionally detrimental effects and providing instrumental resources; and (c) encouraging personal growth.…”
Section: Family Support For Teachersmentioning
confidence: 99%
“…Differentiating the sources of social support is particularly important in studying the social support networks of teachers in Italy, where as mentioned earlier, the family is traditionally considered the principal source of support by many scholars (e.g., Halbesleben, Zellars, Carlson, Perrewé, & Rotondo, 2010;Lo Presti et al, 2016;Sgritta, 1988). However, a particularly comprehensive picture of contemporary social support networks in Italy, based on analysis of national survey data on almost 50,000 individuals reveals that the social support provided by families, considered by the authors as the traditional sources, is increasingly being complemented by extrafamilial support by younger couples, especially in Northern Italy (Amato, Meggiolaro, Rivellini, & Zaccarin, 2017).…”
Section: Family Support For Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…(Zafra, 2016) En consonancia con lo anterior, al interior de la familia se establecen lazos que mantienen la identidad y privacidad, se llevan a cabo acciones con el propósito de lograr una estabilidad relacionada con el compromiso, la seguridad y la socialización de sus miembros (Donalek, 2009). Así, cuando se presenta algún problema, la persona implicada se describe a sí misma como 'favorecida por su familia' (Pernice Duca, 2010), la cual, como institución, tiene responsabilidad sobre el bienestar de sus miembros, y de manera indirecta de la comunidad, proveyendo a sus integrantes las bases para una buena salud y para el ejercicio de prácticas saludables de bienestar (Ackerman, 1995;Garst, Baughman, Franz, & Seidel, 2013;Lo Presti, D'Aloisio, & Pluviano, 2016;Williams, 2003). Por ejemplo, el desarrollo de relaciones seguras entre padres e hijos impacta las interacciones con grupos externos y el desarrollo de habilidades (Matheson, y otros, 2005).…”
Section: Dinámicas Familiaresunclassified